Analysis of AMB-FUBINACA Biotransformation Pathways in Human Liver Microsome and Zebrafish Systems by Liquid Chromatography-High Resolution Mass Spectrometry - Xu, Duo-qi; Zhang, Wen-fang; Li, Jing; Wang, Ji-fen; Qin, Shi-yang; Lu, Jiang-hai (Frontiers in Chemistry, 2019)
In this study, the metabolic profiles of a new illicit drug AMB-FUBINACA were investigated using both human liver microsome and zebrafish models. Liquid chromatography Q Extractive HF Hybrid Quadrupole-Orbitrap mass spectrometry (LC-QE-HF-MS) was employed to analyze the metabolic sites and pathways. AMB-FUBINACA was added to the in vitro liver microsome incubation model to simulate the metabolic processes in human body. The results showed that a total of 17 metabolites were generated in the human liver microsome model; the main metabolic pathways of the phase I metabolism included ester hydrolysis, methylation, ester hydrolysis combined with decarboxylation, hydroxylation, ester hydrolysis combined with indazole ring hydroxylation, etc., while glucuronidation served as the main metabolic pathway of the phase II metabolism. The zabrafish system produced a similar result with 16 of the same 17 metabolites identified. The phase I metabolites M3.1 (ester hydrolysis), M1.2 (alkyl chain hydrolysis ) and the phase II metabolite M3.2 (M3.1 glucuronide) were recommended to be the potential poisoning markers.